Authentic, immersive and emotional experience in virtual learning environments: The fear of dying as an important learning experience in a simulation - Reiners, Torsten; Teras, H.; Chang, Vanessa; Wood, L.; Gregory, S.; Gibson, David; Petter, Natasha; Teras, Marko (The University of Western Australia, 2014)
This paper is about the role of authenticity and emotion to aid learning in immersive virtual environments; in particular the occupational health and safety in the operations and supply chain industry. With the introduction of relatively low cost head-mounted displays such as the Oculus Rift, it is now feasible to introduce environments that are more immersive and authentic; and allow for further experiments on induced and experienced emotions. This article describes an experimental design to evaluate how different levels of authenticity, immersion, and emotion affect learning retention, and how they relate to each other. The container terminal scenario prepares students for site visits, showing the health and safety risks by simulating the consequences of accidents and mistakes in a work place that may cause injury or death.